2022
DOI: 10.3389/fpls.2022.969896
|View full text |Cite
|
Sign up to set email alerts
|

Ion absorption, distribution and salt tolerance threshold of three willow species under salt stress

Abstract: To investigate the response mechanism and salt tolerance threshold of three willow seedlings (Salix matsudana, Salix gordejevii, Salix linearistipularis), the absorption, transport and distribution of salt ions (Na+, K+, Ca2+) were studied under hydroponic conditions with different salt concentrations (CK, 171, 342, 513, and 684 mm) and treatment times (1, 3, 5, 8, 11, and 15 days). Salix linearistipularis has the weakest ability to maintain its apparent shape, while Salix matsudana has the strongest ability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…The absorption and transport of Na + , the main harmful ion to plants under NaCl stress, have always been the focus of research on salt stress. The capacity of a plant to limit Na + absorption, expel Na + from the root system, and prevent Na + from traveling to aboveground components is related to its ability to resist NaCl [ 46 , 47 ]. This study showed that the roots of Magnoliaceae could intercept Na + because the concentration of Na + was greater in roots under NaCl stress than in stems and leaves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption and transport of Na + , the main harmful ion to plants under NaCl stress, have always been the focus of research on salt stress. The capacity of a plant to limit Na + absorption, expel Na + from the root system, and prevent Na + from traveling to aboveground components is related to its ability to resist NaCl [ 46 , 47 ]. This study showed that the roots of Magnoliaceae could intercept Na + because the concentration of Na + was greater in roots under NaCl stress than in stems and leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Plants block the entry of Na + into root cells at low NaCl concentrations by absorbing an excessive amount of K + . However, during severe NaCl stress, a significant amount of Na + enters cells because the plant membrane system breaks down, which lowers the K + level [ 46 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…With more Na + available in the saline treatments, the roots of the purslane plants were able to absorb it in greater quantity ( Table S2 ), confirming the premise that salt stress induces the concentration of Na + ions in the plant cells ( Borsai et al., 2020 ; Giménez et al., 2021 ; Kumar et al., 2021 ). Much of the absorbed sodium remained in the roots, and a small part was translocated to the aerial part of the plants ( Table S2 ), indicating that plants can reduce the damage of salt stress to aboveground tissues by regulating ion transport ( Ran et al., 2021 ; Ran et al., 2022 ). As for Cl − , the roots absorbed only a small part, which translocated to the aerial part of the plants.…”
Section: Discussionmentioning
confidence: 99%
“…For Yassin et al. (2019) and Ran et al. (2022) , low uptake of Na + and high uptake of K + mean salinity tolerance in higher plants.…”
Section: Discussionmentioning
confidence: 99%
“…Although sodium cannot replace potassium in cellular functions, they both share a chemical resemblance that leads to potassium substitution by sodium. Na + and K + compete for root uptake sites and lower the K + and Ca 2+ intake during salinity stress [78]. Similarly, a significant decrease in K + absorption by plants is due to high Na + ions, regardless of whether Na + , chloride, or sulfate ions predominate in soil solutions [71].…”
Section: Nutrient Balancementioning
confidence: 99%